A critical analysis and evaluation of Web-based environments for program development - Deek, Fadi P.; Ho, Ki-Wang; Ramadhan, Haider (The Internet and higher education, 2000)
This paper provides a classification, review, and critical analysis of current Web-based interactive programming environments and tools that facilitate learning programming languages and concepts. The focal point of the paper is based on (1) categorizing available programming systems and tools into classes according to their pedagogical approaches; (2) reviewing individual systems; and (3) critically analyzing them according to established standards for instructional design. The paper is intended to provide those seeking to use these resources with a comprehensive survey of the available systems, their succinct evaluation, and their effectiveness.